2018
DOI: 10.1148/radiol.2018170960
|View full text |Cite
|
Sign up to set email alerts
|

Human Epidermal Growth Factor 2–positive Breast Cancer with Mammographic Microcalcification: Relationship to Pathologic Complete Response after Neoadjuvant Chemotherapy

Abstract: Purpose To determine the relationship between the presence or absence of mammographic calcifications in human epidermal growth factor receptor 2 (HER2)-positive breast cancers and pathologic complete response (pCR) to neoadjuvant chemotherapy and to determine other tumor and clinical characteristics that may be predictive of such a response. Materials and Methods A database of all patients with HER2-positive breast cancer who underwent neoadjuvant chemotherapy between 2007 and 2015 was retrospectively reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 26 publications
2
11
0
2
Order By: Relevance
“…Sometimes when scattered calcification was noted, ultrasound-guided mammotome biopsy was performed with an 11-gauge needle, and > 12 core passes were obtained. It has been reported that radiologically recognized calcifications in breast cancer are associated with HER2 molecular subtype and pCR after neoadjuvant chemotherapy [30,31]. Another reason for collection of multiple cores in CNB is to overcome tumor heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes when scattered calcification was noted, ultrasound-guided mammotome biopsy was performed with an 11-gauge needle, and > 12 core passes were obtained. It has been reported that radiologically recognized calcifications in breast cancer are associated with HER2 molecular subtype and pCR after neoadjuvant chemotherapy [30,31]. Another reason for collection of multiple cores in CNB is to overcome tumor heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Mazari et al reported that the pCR rate in patients with mammographic microcalcification of HER2 þ breast cancer was not different to that in those without calcification. 17 Li et al also reported that patients with calcification had a similar pCR rate to patients without calcifications. 18 These results are in accord with the findings of this study, with 72.0% of the pCR group and 59.1% of the non-pCR group showing calcifications on mammography.…”
Section: Ga Young Yoon Et Almentioning
confidence: 87%
“…This might contribute to different chemosensitivities among molecular subtypes. Mazari et al (31) reported that the HER2+ subtype is a significant predictor for pathologically complete responses, and that the odds ratios increased from 2.49 to 5.4 when univariate regression analysis was changed to multivariate regression modeling. In concordance with previous studies (3,32), our results showed that triple-negative [odds ratio (OR): 2.872, 95% confidence interval (CI): 0.947-16.372] and HER2+ (OR: 3.939, 95% CI: 0.947-16.372) tumors exhibited better responses than hormone receptor-positive, HER2-breast cancer.…”
Section: Discussionmentioning
confidence: 99%